Fever, Sacral Pain, and Pregnancy: An Incarcerated Uterus - Sweigart, Amy N; Matteucci, Michael J (Western Journal of Emergency Medicine, 2008)
Uterine incarceration is an uncommon but serious presentation in the emergency department that requires early recognition to improve maternal and fetal outcomes.Case: A 29-year-old female, at 12 weeks gestation, presented to the emergency department (ED) with complaints of fever, sacral pain and urgency. Based on history and physical examination, she was found to have a retroverted, incarcerated uterus. After a failed attempt at reduction in the ED, her uterus was successfully reduced under general anesthesia.Discussion: Pain and urinary difficulties, such as retention and hesitancy, are frequent in pregnancy, yet incarcerated uterus is an uncommon emergency department diagnosis that often presents with these symptoms. Clues to the diagnosis include a retroverted uterus, urinary retention, and pain in a patient presenting in the third to fourth months of gestation. Treatment is by manual reduction of the uterus. Complications range from spontaneous abortion to uterine rupture.[WestJEM. 2008;9:232-234.]